My sweet girl [large type] - Jayatissa, Amanda (Wheeler Publishing, A part of Gale, A Cengage company, 2021)
Ever since she was adopted from a Sri Lankan orphanage, Paloma has had the best of everything--schools, money, and parents so perfect that she fears she'll never live up to them. Now at thirty years old and recently cut off from her parents' funds, she decides to sublet the second bedroom of her overpriced San Francisco apartment to Arun, who recently moved from India. Paloma has to admit, it feels good helping someone find their way in America--that is until Arun discovers Paloma's darkest secret, one that could jeopardize her own fragile place in this country. Before Paloma can pay Arun off, she finds him face down in a pool of blood. She flees the apartment but by the time the police arrive, there's no body--and no evidence that Arun ever even existed in the first place. Paloma is terrified this is all somehow tangled up in the desperate actions she took to escape Sri Lanka so many years ago. Did Paloma's secret die with Arun or is she now in greater danger than ever before?